Inducible nitric oxide synthase is required for epidermal permeability barrier homeostasis in mice. Issue 10 (30th October 2020) - Dang, Erle; Man, George; Zhang, Jiechen; Lee, Dale; Mauro, Theodora M.; Elias, Peter M.; Man, Mao-Qiang
Abstract: Nitric oxide (NO) regulates a variety of epidermal functions, including epidermal proliferation, differentiation and cutaneous wound healing. However, whether nitric oxide (NO) and its synthetic enzymes regulate epidermal permeability barrier homeostasis is not clear. In the present study, we employed inducible nitric oxide synthase (iNOS) KO mice to explore the role of iNOS in epidermal permeability barrier homeostasis. Our results showed that iNOS mice displayed a comparable levels of basal transepidermal water loss rates, stratum corneum hydration and skin surface pH to their wild‐type mice, but epidermal permeability barrier recovery was significantly delayed both 2 and 4 hours after acute barrier disruption by tape stripping. In parallel, expression levels of mRNA for epidermal differentiation‐related proteins and lipid synthetic enzymes were lower in iNOS KO mice versus wild‐type controls. Topical applications of two structurally unrelated NO donors to iNOS KO mice improved permeability barrier recovery kinetics and upregulated expression levels of mRNA for epidermal differentiation‐related proteins and lipid synthetic enzymes. Together, these results indicate that iNOS and its product regulate epidermal permeability barrier homeostasis in mice.